Effect of implant abutment surface treatments on bacterial biofilm composition and structure - Eduardo Anitua; Alia Murias-Freijo; Roberto Tierno; Ricardo Tejero; Mohammad Hamdan Alkhraisat (Journal of Oral Microbiology)
Background For the long-term success of dental implants, implant abutment surface should promote the attachment of oral epithelial cells and reduce bacterial adhesion. Titanium nitride (TiN) coatings show antimicrobial properties. Nevertheless, there is a lack of clinical trials that assess the biofilm formation on TiN abutments in the context of clinical practice. Thus, the objective of this study was to evaluate the effect of different abutment surfaces (machined, TiN and TiN oxidized) on bacterial biofilm composition and structure.Materials and methods Implant abutments were connected to the dental implants. Bacterial communities were sampled at 1 and 60 days later. The relationship between surface, periodontal indices and bacterial community dynamics was assessed using 16S rRNA metagenomics. A total of 17 patients were involved in this study (14 included in final analyses: 15 machined, 16 TiN and 14 TiN oxidized abutments).Results No significant differences between surfaces were found considering taxa abundance, most alpha diversity metrics or community structure. Time showed a significant effect on diversity and also on the abundance of several bacterial taxa.Conclusions These results indicate that the effect of the three tested abutment surfaces on biofilm structure and composition was negligible, whereas patient and time exert strong influences on bacterial biofilm formation at different scales.